2013
DOI: 10.1016/j.lwt.2012.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drying conditions and plasticizer type on some physical and mechanical properties of amaranth flour films

Abstract: a b s t r a c tIn this work we studied the influence of the drying temperature and relative humidity on the solubility, mechanical properties, water vapor permeability (WVP), and drying time of amaranth flour films plasticized with glycerol or sorbitol. The effect of drying temperature and relative humidity on the mechanical properties of the film is a function of the plasticizer type. In the presence of glycerol, tougher flour films are obtained at a lower drying rate, but an inverse behavior is observed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
48
4
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 32 publications
8
48
4
6
Order By: Relevance
“…The tensile strength values of plasticized SPS films were higher than the reported values for films of corn starch with glycerol and stearic acid [69], corn starch with glycerol and xylitol [62], corn starch with glycerol alone [70], glycerol plasticized rice starch [71], amaranth flour plasticized with sorbitol or glycerol [68], cassava starch with glycerol [72], cush-cush yam starch [73], and pea starch with glycerol [74]. On the other hand, their tensile strength values were lower than LDPE and polystyrene [63].…”
Section: Tensile Strength Of Sugar Palm Starch (Sps) Plasticized Filmscontrasting
confidence: 59%
See 2 more Smart Citations
“…The tensile strength values of plasticized SPS films were higher than the reported values for films of corn starch with glycerol and stearic acid [69], corn starch with glycerol and xylitol [62], corn starch with glycerol alone [70], glycerol plasticized rice starch [71], amaranth flour plasticized with sorbitol or glycerol [68], cassava starch with glycerol [72], cush-cush yam starch [73], and pea starch with glycerol [74]. On the other hand, their tensile strength values were lower than LDPE and polystyrene [63].…”
Section: Tensile Strength Of Sugar Palm Starch (Sps) Plasticized Filmscontrasting
confidence: 59%
“…This tendency can be ascribed to the smaller molar mass of glycerol (92.0928 g/mol; sorbitol 182 g/mol) which facilitate easy interaction between glycerol-starch molecular chains. Tapia-Blácido et al [68] also testified that glycerol is a more effective plasticizer for most edible films. [68] and Tapia-Blácido et al [50], who reported that sorbitol plasticized flour films are more resistant to breakage than films plasticized with glycerol at constant proportions.…”
Section: Tensile Strength Of Sugar Palm Starch (Sps) Plasticized Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant difference was not found between the tensile strengths during the storage. HPC described as having less water affinity in the literature [70] and this behaviour of filmforming polymer was evidenced with tensile strength measurement, because the Gly content of the films dramatically decreased the tensile strength of films via increasing of water absorption which is also written in the literature [85][86][87].…”
Section: Tensile Strengthmentioning
confidence: 94%
“…Például β 1 -receptor stimuláció a nyálmirigy megnagyobbodását idézi elő, míg a metoprolol (β 1 antagonista) csökkenti a mirigyállo-mány méretét [86,87]. A nyálmirigy állomány megnagyobbodását okozó hatóanyagok a VII.…”
Section: Nyálmirigyek Morfológiai Változásaunclassified